Analysis of Macroeconomic Variables on the Existence of Inflation in Indonesia Using the Vector Error Correction Model Approach - Afrizal, Afrizal (Jurnal Ekonomi Kuantitatif Terapan, 2024)
This research investigates the impact of macroeconomic variables, namely money supply, exchange rate, interest rate, and the joint stock index, on inflation in Indonesia. Employing the Vector Error Correction Model (VECM) dynamic model approach, the study reveals a long-term relationship among each variable (Inflation Rate, Jakarta Composite Index, Interest Rate, Exchange Rate, and Money Supply). Granger Causality Test results indicate a unidirectional relationship of interest rate and money supply variables to inflation, interest rate to Jakarta Composite Index, and money supply to the exchange rate. Conversely, there is a bidirectional relationship between exchange rate and inflation variables. In the short term, Interest Rate significantly and positively influences inflation, whereas, in the long term, it exhibits a negative and insignificant effect. Money supply, in the long run, significantly and positively affects the inflation rate. This study stands out in the macroeconomic literature due to its distinctive choice of variables and the dynamic model employed